CSF Biomarkers Profile in CADASIL—A Model of Pure Vascular Dementia: Usefulness in Differential Diagnosis in the Dementia Disorder - Formichi, Patrizia (SAGE-Hindawi Access to Research, 2010)
Cerebral Autosomal Dominant Arteriopathy with Subcortical Infarcts and Leukoencephalopathy (CADASIL) is considered a model of pure vascular dementia (VD) because it occurs in young adults unlikely to have concomitant age and Alzheimer's Disease-(AD-) related pathology. CSF levels of β-amyloid 1-42 (Aβ42), total tau protein (t-tau), and phosphorylated tau-protein (p-tau), well accepted biomarkers of AD, were evaluated in 10 CADASIL patients, 22 AD patients, and 17 healthy age-matched subjects. Innotest β-amyloid 1-42, Innotest hTAU-Ag, and Innotest Phospho-tau 181p sandwich enzyme-linked immunoassay were used to determine CSF biomarkers levels. A case-control statistical analysis was carried out. CSF Aβ42 levels were significantly lower in CADASIL patients and considerable overlap with AD whereas t-tau and p-tau levels were normal and significantly different with respect to AD. A significant altered CSF biomarkers profile in a pure VD supports the use of CSF Aβ42, t-tau, and p-tau levels in the differential diagnosis of VD and AD.